Letter to the Editor: Human Pluripotent Stem Cells Release Oncogenic Soluble E-Cadherin. (27th July 2016) - Rosner, Margit; Hengstschläger, Markus
Abstract: Since their discovery, human pluripotent stem cells (hPSCs) including embryonic and induced pluripotent stem cells hold great promise in disease modeling and regenerative medicine. Despite intensive research and remarkable progress, it is becoming increasingly acknowledged that their yet incomplete, biological characterisation represents one of the major drawbacks to their successful translation into the clinics. The expression of the transmembrane protein E-cadherin in hPSCs is well defined to be pivotal to the maintenance of the pluripotent state by mediating intercellular adhesion and intracellular signaling. Next to these canonical functions, were here report for the first time that hPSCs are subject to matrix metalloproteinase-dependent E-cadherin ectodomain shedding. This generates a ∼80-kD, soluble E-cadherin fragment which is released into the extracellular space, and which is well described to exert paracrine signaling activity and classified as being oncogenic. Collectively, this finding does not only improve our knowledge on the signaling crosstalk between hPSCs and their cellular environment and the type and nature of the paracrine signals produced by these cells, but also has clear implications for the development of efficient and safe stem cell-based therapies. Abstract : E-cadherin ectodomain shedding in hPSCs with implications for basic research and therapy. hESCs and hiPSCs express E-cadherin on the cell surface known to be pivotal to the maintenance of the pluripotent state by mediating intercellular adhesion (1) and intracellular signaling (2). Next to these known, canonical functions of the full-length protein, the E-cadherin ectodomain is proteolytically cleaved upon MMP-mediated processing and released into the extracellular space (termed ectodomain shedding) (3). This E-cadherin fragment of 80 kD (soluble E-cadherin) is well documented to exert paracrine signaling activities by activating receptor tyrosine kinases and downstream signaling cascades leading to enhanced cell survival, proliferation and invasion, and is classified as being oncogenic. Taken together, this observation of E-cadherin ectodomain shedding in hPSCs strongly suggests the involvement of soluble E-cadherin in the signaling crosstalk between stem cells and their therapeutic and/or natural environment including putative roles in hPSC tumorigenicity and embryonic development.